2016
DOI: 10.2174/1573406411666150518105010
|View full text |Cite
|
Sign up to set email alerts
|

α¯ Aminoisobutyric Acid Leads a Fluorescent syn-bimane LASER Probe Across the Blood-brain Barrier

Abstract: Penetration of the blood brain barrier (BBB) by appropriate fluorescent probes remains a challenge in optical imaging and diagnostics. We designed, synthesized and observed the in vivo BBB penetration of a LASER syn-bimane probe. Results demonstrate that the Aib transporter unit in our probe may lead a fluorescent bimanyl moiety across the BBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Today, two agents (see below) that might be useful as probes to detect their biomarkers of neurodegenerative diseases were prepared by two groups. Recently, such small molecules that could be supplied to the brain via the blood streams (abdominal or tail injection) have been reported by an Israeli and a Korean groups and introduced to the inner brain by crossing the blood brain barrier (BBB) [62,63].…”
Section: Styrylbenzene Derivative and Ethidium Bromidementioning
confidence: 99%
“…Today, two agents (see below) that might be useful as probes to detect their biomarkers of neurodegenerative diseases were prepared by two groups. Recently, such small molecules that could be supplied to the brain via the blood streams (abdominal or tail injection) have been reported by an Israeli and a Korean groups and introduced to the inner brain by crossing the blood brain barrier (BBB) [62,63].…”
Section: Styrylbenzene Derivative and Ethidium Bromidementioning
confidence: 99%
“…The penetration of microbes into the inner brain can be the Currently, many agree that the gut microbiome reaches the brain using the "gut-brain axis" and is the cause for the onset of neurodegeneration -this penetration results in inflammation, then infection and apoptosis of the brain tissue. Antimicrobial peptide surrogates [15,16], based on a brain-penetrating scaffold-like diazepine [17,18] or 1,4 dihydropyridine [19][20][21] may be suitable to combat the invading microbiota and in a later stage serve as antimicrobial agents to combat the infection and prevent aggregation [22]. It was shown that some selectivity in bacteria eradication was possible [23].…”
Section: Figurementioning
confidence: 99%
“…These sensors, which operate in both solution-state and on filter papers to provide fluorometric and colorimetric analyte detection, have notable practical advantages, including their high sensitivity, ease of access, and non-toxicity of both the bimane transducing element and supramolecular cyclodextrin scaffold. The lack of toxicity of both cyclodextrin ( Kfoury et al, 2019 ) and bimane (MSDS 38369) has been well-established in the literature, and has led to the use of both of these components in a variety of biologically-relevant applications ( Barbosa et al, 2019 ; Lapidot et al, 2016 ; Lavis and Raines 2008 ). Moreover, an additional report from one of our research groups has demonstrated a streamlined approach to access bimane derivatives, which facilitates practically attainable access to a variety of these highly fluorescent structures ( Szumski et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%